STOCK ABUNDANCE INDEX, DENSITY, COMPOSITION, AND DISTRIBUTION OF DEEP-SEA SHARK AND RAY RESOURCES IN THE EASTERN INDIAN OCEAN - Suprapto Suprapto; Badrudin Badrudin (Indonesian Fisheries Research Journal, 2006)
Deap-sea shark and ray resources in lhe Indian Ocean provide one of the most economically important fish mesopelagic and demersal resources. Deta analyzed were pad of the survey carried out in May to June 2005 in the frameworkd6op.soa rays, sharks, stock abundance index, ltock denllty, species composition, distributon, aouthern Java, western Sumatera, Eastam Indian Ocean of The Japan-lndonesia Deap Sea Fisheries Rosources Joint Explontion Marine Resedrch 2004.